Oportunidades e desafios da prática do Marketing Verde no setor hoteleiro de pequeno porte - Pereira, Lindinalva (2017)
The basis of sustainable development is formed by the abandonment of the predominance of classical economic theory. The stimulus required in our present world has its most basic principle based on the concept where social, environmental and economic are intrinsically linked. The impact of the theme, the passion for tourism and the relative updating of the subject with the publication of Agenda 30 by the UN, gave rise to this work whose focus was on the questioning about the contribution of small lodging facilities to social and environmental issues, exploring the practical application of the hotel actions, projects and business strategies. This work was associated with a critical evaluation of how the Green Marketing could contribute to add value to the business, generating competitive differential and better positioning for companies in the sector. It is based on the theories of Service Marketing, Green Marketing, Social Responsibility, Sustainable Development and Tourism I developed a more comprehensive conception of the theme and a maturity in relation to the representativeness of the subject for the different stakeholders involved. Endowed with this important base, the work was developed focusing on the small lodging called Hotel Fazenda Campos/Parque dos Sonhos located in the city of Socorro, in the state of São Paulo, Brazil. To Observe. To explore. To interview. The basic premise was that the socio-environmental practices of the establishment were operative and recognized by any competent institutions. The broad reflection in search of leading or innovative initiatives allowed us to infer some guidelines that may be decisive for the implementation of Green Marketing strategies in small lodgings: the entrepreneurship of the owner and the benefits of social and environmental certification processes. The necessary process review allows optimization of the whole chain and the cost reduction, as well as a spontaneous exposure of the company to its stakeholders